Prenatal Exposure to Acid Suppressor Medications and Development of Ductus Arteriosus in Term Newborns - Segal, Ella; Landau, Daniella; Hassan, Lior; Israeli, Adir; Gorodischer, Rafael (American Journal of Perinatology, 2024)
Objective The ductus arteriosus normally closes after birth. Histamine 2 receptor antagonist (H2RA) has been associated with patent ductus arteriosus (PDA). We aimed to study the characteristics of term infants with PDA and their possible association with prenatal exposure to antacids—proton pump inhibitors (PPIs) and H2RA.Study Design This was a population-based matched case–control study of mothers registered at “Clalit” Health Maintenance Organization (HMO) and their infants born at “Soroka” University Medical Center (SUMC) between 2001 and 2018. Cases are defined as term infants born with PDA diagnosed by echocardiography and registered in the postdelivery discharge form. Each case was matched with four term newborns without PDA diagnosis. Exposure window was defined by the timing of first purchase of H2RA or PPI during pregnancy and based on information from a computerized medication database (Clalit HMO, SUMC).Results PDA was diagnosed in 1,884 term infants (4.9%). Characteristics included a significantly higher percentage of lack of prenatal care, cesarean section, in vitro fertilization, polyhydramnios, oligohydramnios, Apgar 1 minute <5, and prenatal exposure to H2RA (odds ratio [OR] 4.18) and PPIs (OR 3.50; all p < 0.001). PDA association with exposure window was similar in each trimester (1.5–2%) for both H2RA and PPI.Conclusion PDA incidence in term infants in our population was greater than previously reported. PPI and H2RA are both antiacids with different mechanisms of action. The similar OR for exposure to one as well as the other, and the lack of influence of the initial exposure period, are compatible with bias.Key Points
Keywords: patent ductus arteriosus; antiacids; histamine 2 receptor antagonist; proton pump inhibitors; prenatal exposure